(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
The development of modern society, socio-economic development, the rise of science and technology directly depend on the level of human capital. One of the main pillars of human capital is the education system. Education involves not only imparting certain knowledge, but also forming a person as an independent thinker, capable of research, and capable of creating innovations. From this point of view, the formation of experimental-research skills in students and pupils is one of the important pedagogical tasks. Because these skills increase the interest of young people in scientific and creative activities, develop in them the ability to apply theoretical knowledge in practice, analyze problems and find effective solutions.